Kurikulum Pendidikan Islam Multikultural (Analisis Tujuan Taksonomi dan Kompetensi Peserta Didik) - Tri Wahyudi Ramdhan (STAI Ma'had Aly Al-Hikam Malang, 2019)
This article will to discuss the curriculum of multicultural Islamic education. Considering the curriculum discussion is very diverse, from a narrow and broad scope, however in general the scope or component of the curriculum consists of elements (1) goals; (2) content or material; (3) material delivery process or system; and (4) evaluation. And in this paper not all elements of the curriculum are of concern, the discussion will only be focused on elements of objectives that will be associated with multicultural Islamic values. Thus the focus that is the main target of the author in this discussion is about goals, precisely about the hierarchy of the formulation or formulation of educational goals, and taxonomy to develop learning objectives and the preparation of instruments for evaluation of multicultural Islamic learning outcomes.Â Pada tulisan ini membahas tentang kurilum pendidikan Islam multikultulral. Mengingat pembahasan kurikulum sangat beragam, dari cakupan sempit maupun luas, namun demikian secara umum cakupan atau komponen kurikulum terdiri dari unsur (1) tujuan; (2) isi atau materi; (3) proses atau sistem penyampaian materi; dan (4) evaluasi. Dan dalam tulisan ini tidak seluruh elemen kurikulum tersebut menjadi perhatian, pembahasan hanya akan difokuskan pada elemen tujuan yang akan dihubungkan dengan nilai-nilai Islam multikultural. Dengan demikian fokus yang menjadi sasaran utama penulis dalam pembahasan ini adalah mengenai tujuan, tepatnya tentang hirarki penyusunan atau perumusan tujuan pendidikan, serta taksonomi untuk menyusun tujuan pembelajaran serta penyusunan intrumen evaluasi hasil pembelajaran Islam multikultural.